1987
DOI: 10.1021/ac00135a004
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed laser desorption of biological molecules in supersonic beam mass spectrometry with resonant two-photon ionization detection

Abstract: Pulsed laser desorption Is used to volatllke small Momdecules for supersonlc Jet Injection Into a mass spectrometer. Following desorption of the molecular plume Into the Jet, the molecules are Ionized by resonant two-photon lonlzatlon (RPPI) In a tbne-of-flight mass spectrometer. Several ultraviolet wavelengths have been used to study the lonlzatlon properties of dlfferent groups of blomolecules lncludlng the aMllty to obtaln Son lonlzation and laser wavelength selective lonlzatlon. I n addition, fragmentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 32 publications
1
47
1
Order By: Relevance
“…As shown in previous studies [20,22], soft ionization mass spectra of adenine and cytosine were observed using laser desorption followed by R2PI at modest laser energy (-lo6 W cmm2). In addition, ionization of guanine was also observed at 266 nm due to the optimization of the desorption/entrainment of sample into the jet over that attained in previous work.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…As shown in previous studies [20,22], soft ionization mass spectra of adenine and cytosine were observed using laser desorption followed by R2PI at modest laser energy (-lo6 W cmm2). In addition, ionization of guanine was also observed at 266 nm due to the optimization of the desorption/entrainment of sample into the jet over that attained in previous work.…”
Section: Resultssupporting
confidence: 64%
“…The supersonic beam time-of-flight mass spectrometer is similar to that used in previous experiments [22]. It consists of a differentially-pumped TOFMS mounted vertically in a stainless steel six-port cross pumped by a 6-in diffusion pump.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous single-color MPI experiments using ns laser pulses at 222 nm, 13 248 nm, 14 and 235-268 nm 12 did not produce any discernible uracil cation signals, whereas Brady et al 15 were able to record a REMPI spectrum with a 270-285 nm pump and a 193 nm probe (both ns-timescale pulses). Fig.…”
Section: A Non-dissociative Mpi Of Isolated Uracilmentioning
confidence: 91%